一种基于案事件时空坐标的目标人轨迹碰撞分析方法 (2023)
本发明涉及一种基于案事件时空坐标的目标人轨迹碰撞分析方法，属于异常行为主体分析技术领域，包括以下步骤：预处理案件数据和轨迹数据，确保时间信息和空间信息具有碰撞和进一步时空关联分析的前提；将预处理后的案件数据和轨迹数据进行时间碰撞，保留落在案发时间范围内的轨迹信息；在时间碰撞的基础上将案件数据和所述轨迹数据进行空间碰撞，保留落在指定空间范围内的轨迹信息；根据时空范围内的轨迹主体信息，利用四种时空关联分析方法进一步挖掘异常主体。本发明将传统的时空碰撞分析方法和四种时空关联分析方法相结合，极大地减少了异常行为主体排查范围，减轻了侦查破案的工作量。 The invention relates to a target person trajectory collision analysis method based on case event space-time coordinates, and belongs to the technical field of abnormal behavior subject analysis, and the method comprises the following steps: preprocessing case data and trajectory data, and ensuring that time information and space information have the premise of collision and further space-time correlation analysis; performing time collision on the preprocessed case data and the track data, and reserving track information within the crime occurrence time range; on the basis of time collision, subjecting case data and the trajectory data to space collision, and reserving trajectory information falling in a specified space range; and according